KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI SEGITIGA - Nia Imanisa; Kiki Nia Sania Effendi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study was to determine students' mathematical communication skills in solving problems on triangle material. The research subjects were 30 students in class VIII C at one of junior high schools in Karawang. This research uses a descriptive method with a qualitative approach. The instrument used is a test instrument. The data collection technique was carried out by giving 3 triangular material description questions to students. The data analysis technique uses descriptive data analysis which is used by describing the sample data into a form that is easier to understand. The results of this study indicate that the average score of students' mathematical communication skills test is 68.43 this average value is above the Minimum Completeness Criteria (KKM) value of 65. Based on the results of the categorization of students according to mathematical communication skills, get the percentage 23.34% of students are included in the high category level, while students who are included in the moderate category level are a percentage of 63.33%, and 13.33% of other students are included in the low category level, so it can be concluded that the mathematical communication abilities of 30 people students in class Vlll C in solving questions on triangle material are included in the medium category level.